0.5 μm GaN RF power bar technology space evaluation. (November 2020) - Van de Casteele, J.; Stuhldreier, H.; Bouw, D.; Gourdon, C.; Raoult, M.; Durand, E.; Van Den Berghe, S.; Hollmer, M.; Grunwald, M.; Lambert, B.; Blanck, H.; Barnes, A.
Abstract: This paper describes the test plan and the main results achieved by UMS during a space evaluation of its second generation 0.5 μm GaN RF power bar technology, called GH50-20. The space evaluation tests results are summarised: a life time higher than 5.10 6 h @ 200 °C is found, SEE, TID and DD radiation hardness safe area were defined, and failure rate below 10 FIT @ 200 °C was determined. The results also include demonstration of representative integrated circuits up to 130 W RF power level when operated in L-band in continuous wave (CW) mode. The GH50-20 technology has successfully passed the space evaluation program and is deemed suitable for use in space. Highlights: A formal space evaluation campaign has been successfully performed on the UMS 0.5 μm GaN RF power bar technology A failure rate of 9 FIT is evaluated for an operation at Tj = 200 °C with a confidencelevel of 60% Lifetime is evaluated higher than 5.0 · 10 6 hours when operating at Tj = 200 °C Displacement Damage and Total Ionizing Dose tests show no influence of proton and Co60 irradiation on electrical performances Single Event Effect tests results allowed to define a secure area of operation under heavy ions environment